EVALUATION OF OIL ACCUMULATION IN THE TROPICAL MARINE DIATOM CELLS OF Thalassiosira sp. UNDER OUTDOOR CULTURE CONDITIONS - KUSUMANINGTYAS (NIM: 30513001), PINTAKA
A tropical marine diatom of Thalassiosira sp. grown indoor capable of producing oil (fluid-neutral lipids) that suitable for biodiesel feedstock. To produce the huge biomass of Thalassiosira sp., the cells should be cultivated in a large scale under fertilizer-based medium and direct sunlight exposure for photosynthesis. However, so far, no published data on nutrients derived from agricultural fertilizers leading to the oil accumulation in the Thalassiosira sp. cells cultured outdoors. As known that algal cultures grown outdoors are usually exposed to a combination of environmental stress, including high sunlight intensity and temperature, that affect on lowering of photosynthesis rate, reducing of biomass productivity, and altering of pathways and activities of cells metabolism causing the changes of food reserved products, in particular oils and fatty acids. Therefore, the present study aimed to discover nutritions that are able to lead the metabolism of Thalassiosira sp. cells on the accumulation of oils with high productivity. This research methods consist of three stages. Firstly, evaluate three types of fertilizer-based media under laboratory condition to find a suitable fertilizer-based medium for the growth of Thalassiosira sp. cells. The fertilizer medium showing the best cell growth was then evaluated to determine the nutritional components that play a role in the production of biomass and oil from Thalassiosira sp. Secondly, evaluate the nutritional status of Thalassiosira sp. culture to determine the sufficiency of three important macronutrients (phosphate, nitrate, and silicate) for the cell growth under outdoor stress conditions. The nutrients found to be deficient, further optimized to get an optimum nutrient concentration for cell growth and oil production under environmental stress condition indoors. Finally, Thalassiosira sp. cells grown using optimum nutrient concentration were evaluated outdoors under various weather and season conditions to determine the productivity of oils accumulated in the cells. Three types of fertilizer-based media evaluated in this study, namely P1 medium (urea fertilizer, TSP fertilizer and Si-P-PG fertilizer), P2 medium (NPK fertilizer and Si-P-PG fertilizer), and P3 medium (NPK fertilizer and sodium metasilicate). Those fertilizer-based media were developed based on a previously published enriched seawater (ES) medium. The evaluation showed that P3 medium was able to produce the highest cell productivity with total lipid productivity of 10.4 ± 0.9 mg L–1 h–1, indicating that P3 medium was suitable for Thalassiosira sp. cells growth. The evaluation of nutritional components contained in P3 medium showed that nitrate plays a role in improving biomass yield, and trace minerals play a role in increasing the total lipid content. Both components of the nutrient also play a role in increasing the proportion of polyunsaturated fatty acids (PUFAs) in total fatty acid of Thalassiosira sp. The evaluation of nutritional status in the outdoor cultures showed that the cultures has silicate deficiency.Consequently,the optimization of silicate concentration was conducted under indoors culture condition by increasing the silicate concentration from 10 mg/L to 45 and 120 mg/L. Culture grown in P3 medium with lower silicate concentration (10 and 45 mg/L) showed high oils accumulation in the cells. However, culture in medium with silicate concentration of 45 mg/L can produce significantly higher biomass than that of 10 mg/L under high light stress conditions. P3 medium with silicate concentration of 10 mg/L can lead Thalassiosira sp. cell on high PUFA accumulation, especially AA, EPA, and DHA, under high light stress conditions, so it is potentially used as a source of omega-3, whereas P3 medium with silicate concentration of 45 mg/L lead Thalassiosira sp. cells on the accumulation of oil with high saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) both in high and low light stress conditions, so it is suitable as biodiesel feedstock. To discover nutritions that are able to lead the metabolism of Thalassiosira sp. cells on the accumulation of oils with high productivity in outdoors, Thalassiosira sp. were cultured in media with different N source (ES-nitrat medium and ES-urea medium).The cells cultured in ES-urea medium showed slower cell growth and higher chlorophyll content, so it triggered higher oils accumulations in the cells. Different sources of N also regulate the fatty acid composition of the cells. Cultures in ES-urea medium are able to accumulate PUFA-enriched oils, especially AA, EPA, and DHA, in the exponential phase, indicating that lipid biosynthesis in the cells was faster. This contrasts to the culture in ES-nitrate medium showing faster cell growth and accumulation of DHA only in the stationary phase. This finding provided the information on N sources that can lead the cell metabolism to produce high biomass and oils outdoors. Furthermore, combination of both nitrate and urea as N source in P3 medium was evaluated under outdoors condition with different silicate concentration (10 mg/L and 45 mg/L). Thalassiosira sp. cells cultured in P3 medium with silicate concentration of 10 mg/L was capable of accumulating PUFA-enriched oils, especially AA, EPA and DHA, in rainy season with total lipids productivity of 6.6 ± 1.9 mg L-1 h-1, whereas in the dry season, the fatty acid profile changed to more saturated with lower total lipids productivity, which was 2.2 ± 1.9 mg L-1 h-1. In contrast, the culture in P3 medium with silicate concentration of 45 mg/L can produce oils with more stable fatty acids composition dominated SFA and MUFA both indoors and outdoors,with similar total lipids productivity was reaching 10.86 ± 2.50 mg L-1 h-1. However, oils contained in total lipids from Thalassiosira sp. cultured outdoors was higher than that cultured indoors, so this outdoor cultures can produce oils with the productivity of 1.5 times higher, indicating that the cultivation of Thalassiosira sp.outdoors is feasible to produce oils in a large scale either as a sources of omega-3 or as biodiesel feedstock.